Paving the way for research findings: writers' rhetorical choices in education and applied linguistics - Lim, Jason Miin Hwa (2011)
Notwithstanding the existence of previous investigations into how research results are presented in different academic disciplines, fewer studies have looked into how authors pave the way for their results, the interdisciplinary differences in ‘result pavements’, and the interconnections between their communicative functions and linguistic choices. Using the techniques of genre analysis, I have analyzed two corpora of research reports in applied linguistics and education in order to identify the possible ways in which experienced writers schematically pave the way for their findings. Using evidence based on authentic research articles, this study demonstrates how writers set the stage for their research results by (i) demonstrating their control of the structure and flow of result-related information, (ii) connecting past research with a current finding while furnishing pertinent background elements that lead the readership progressively to specific findings, (iii) regenerating readers’ interest in their initial research purposes, and (iv) deploying locatives to embed results in a ‘space-saving strategy’ aimed at presenting an abridged Results section. I have also analyzed interdisciplinary differences in the frequencies of these rhetorical steps and the range of intricate linguistic mechanisms employed by authors as communicative resources in each step to establish a smooth rhetorical transition that sets the stage for their research results.